The Effect of Firm Size, Profitability, Audit Quality, and Dividend Policy on Earnings Management at Indonesian Conventional Banking - Candra Yoga Prasetyo; Januar Eko Prasetio (International Journal of Applied Business and International Management, 2025)
Earnings management is a major concern for stakeholders, as it can reduce the credibility of financial statements and affect investment decision-making. Even though financial reporting regulations are being tightened, earnings management remains a phenomenon because it negatively affects the quality of corporate earnings and investor trust. Therefore, ongoing effort is needed to identify factors that influence or limit these practices, specifically in Indonesian conventional banking. This study aims to empirically test the simultaneous and partial influence of the structural factor (firm size), performance factor (profitability), external governance factor (audit quality), and managerial policy factor (dividend policy) on earnings management in conventional banking companies listed on the IDX from 2020–2024. This research uses purposive sampling with 105 samples that meet the criteria. Overall, this research shows that the factor influencing earnings management in Indonesian conventional banks is only firm size, with a significance value of 0.000, which is below 0.05. The significance value for profitability is 0.466, for audit quality 0.624, and for dividend policy 0.356; these three variables have values above 0.05. The independent variables in this research show that the overall effect on earnings management is still weak and needs improvement by incorporating other variables for future researchers.